DIGITAL FABRICATION AS A LEARNING MEDIA FOR LIGHTWEIGHT STRUCTURE WITH CASE STUDY OF SHELL STRUCTURE - Stephanus Evert Indrawan; LMF Purwanto (MODUL, 2021)
The lightweight structure system is an effort to optimize the structure to distribute the load efficiently. Unfortunately, students often have difficulty imagining the learning outcomes application in the real world when studying light structural systems. However, the use of the scalar model can still explain several essential aspects of a lightweight structural system, one of which is the effect of connection and formation of material components on the structural capability. Therefore, this paper aims to bridge the learning process by utilizing digital devices from the concept stage of structural modeling with the help of software (Rhinoceros, Grasshopper, and Kangaroo) to the realization process using laser cutting. The method used is a semi-experimental method that applies Hooke's law principle, which produces a shell structure system with a digital fabrication approach that utilizes a lightweight material, namely, corrugated paper board, as the primary material. This paper concludes that digital technology and digital fabrication processes can help students understand the concept of lightweight structures because they can use computer simulations, cut them using laser cutting, and assemble them in the field in a series of simultaneous processes.